16-Hydroxycembra-1,3,7,11-tetraene, a new Cembrane Diterpene from Malaysian Soft Coral Genus Sarcophyton - Takashi Kamada; Chin-Soon Phan; Tin, Hoe Seng; Charles Santhanaraju Vairappan; TengkuSifzizul Tengku Muhammad (2016)
One new cembrane diterpene, 16-hydroxycembra-1,3,7,11-tetraene (1), along with three known compounds, 15-hydroxycembra-1,3,7,11-tetraene (2), sarcophine (3) and sarcophytoxide (4) were isolated from Sarcophyton sp. collected from Karah Island, Terengganu, West Malaysia. Their structures were elucidated based on spectroscopic data. Activities of these compounds against antibacterial resistant clinical bacteria are reported. Only 1 exhibited inhibition against Staphylococcus aureus.